Pediatric Oncology Nursing Advanced Clinical Handbook - Tomlinson, Deborah; Kline, Nancy E.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
This is the second edition of a comprehensive clinical handbook for nurses in pediatric hematology/oncology that presents in-depth information on pathophysiology, diagnosis, treatment, advanced assessment, and interventions. All chapters have been updated since the first edition, and additional chapters have been included where necessary. The book is divided into five sections: pediatric cancers, hematologic disorders, treatment of childhood cancer, side-effects of treatment and disease, and supportive and palliative care. It is organized in a consistent and accessible format with quick reference guides that will prove invaluable in everyday practice. Future perspectives and opportunities for new treatment options and research are also presented. All of the authors are pediatric experts from the United Kingdom and North America, and their contributions reflect their diverse backgrounds and experiences. This handbook will provide an indispensable tool for those responsible for the clinical nursing care of children with cancer, and assist in meeting the many challenging developments in this specialty.
Leukemia -- Leukemia -- Lymphoma -- Solid Tumor -- Central Nervous System Tumors -- Anemias -- Anemias -- Neutropenia -- Thrombocytopenia -- Bleeding Disorders -- Chemotherapy -- Chemotherapy -- Radiotherapy -- Hematopoietic Stem Cell Transplantation -- Surgical Approaches to Childhood Cancer -- Cell and Gene Therapy -- Biological and Targeted Therapies -- Complementary and Alternative Medicine -- Clinical Trials -- Metabolic System -- Metabolic System -- Gastrointestinal Tract -- Bone Marrow Function -- Respiratory System -- Renal System -- Cardiovascular System -- Central Nervous System -- Musculoskeletal System -- Skin: Cutaneous Toxicities -- Endocrine System -- Ototoxicity -- Ocular Complications -- Nutrition and Hydration in Children with Cancer -- Nutrition and Hydration in Children with Cancer -- Pain in Children with Cancer -- Blood Transfusion Therapy -- Cytokines -- Care of the Dying Child and the Family.
Keywords: Medicine; Nursing; Oncology; Pediatrics; Medicine & Public Health; Oncology; Nursing; Pediatrics